Pemikiran Pendidikan Kritis dari Barat ke Timur: Telaah Teoritis dan Praksis dalam Pendidikan Indonesia - Imama, Mohammad Luthfi; Pribadi, Pandu; Herdiman, Herri (Innovations in Multidisciplinary Education Journal, 2025)
This study examines the thoughts of six critical education figures from both the East and the West (Paulo Freire, Henry Giroux, Ira Shor, K.H. Ahmad Dahlan, Ki Hadjar Dewantara, and Mochtar Buchori), analyzed within the framework of ontology, epistemology, and axiology of critical education. Using a literature review and thematic analysis, this article reveals that although they come from different social and cultural contexts, these six thinkers share a common vision of education as a tool for emancipation and social transformation. Furthermore, the article explores how these ideas can be implemented within the Indonesian education system, which is still overshadowed by technocratic approaches and the dominance of market ideology. The findings recommend integrating the values of critical education into curriculum design, learning strategies, and national education policies as an effort to foster students’ critical consciousness and promote social justice.